"Cat Scratch Colon" and Cecal Barotrauma perforation during colonoscopy using CO2 insufflation. (11th September 2014) - Murphy, Christopher John; Cox, Kristen; Fang, John C
Cecal perforation due to barotrauma is an increasingly recognized complication of colonoscopy when using room air for insufflation. CO2 is increasingly being utilized for insufflation due to more rapid absorption compared to ambient air and results in reduced post-procedural pain and flatulence. Use of CO2 is thought to protect against barotrauma injury, and use of CO2 during endoscopy has not previously been reported to cause barotrauma perforation during colonoscopy. We present a case of cecal perforation secondary to barotrauma during routine screening colonoscopy with CO2 .